2013
DOI: 10.1002/pon.3253
|View full text |Cite
|
Sign up to set email alerts
|

Screening for depression and anxiety in women with breast and gynaecologic cancer: course and prevalence of morbidity over 12 months

Abstract: Women are most vulnerable to psychological morbidity at diagnosis. Symptoms improve significantly over time. Reported rates are lower than those in the literature. Regular screening by self-report is acceptable to patients but may not be the most efficient method of improving patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 63 publications
8
45
1
Order By: Relevance
“…The authors found that anxiety and depression symptoms were highest at diagnosis with significant improvements observed by 8 and 24 weeks, respectively and maintained thereafter. The authors argued that the depressive symptoms did not decrease significantly at the beginning of the cancer due to the inclusion of physical symptoms in the assessment tool like CES-D, which they frequently encountered during the early treatment stage of cancer like surgery and chemotherapy [34]. However, in the current study, we studied the depressive symptoms using the HADS depression subscale, which does not contain somatic symptoms in the assessment [27].…”
Section: Discussionmentioning
confidence: 85%
“…The authors found that anxiety and depression symptoms were highest at diagnosis with significant improvements observed by 8 and 24 weeks, respectively and maintained thereafter. The authors argued that the depressive symptoms did not decrease significantly at the beginning of the cancer due to the inclusion of physical symptoms in the assessment tool like CES-D, which they frequently encountered during the early treatment stage of cancer like surgery and chemotherapy [34]. However, in the current study, we studied the depressive symptoms using the HADS depression subscale, which does not contain somatic symptoms in the assessment [27].…”
Section: Discussionmentioning
confidence: 85%
“…Many feel that cancer is a death sentence and poses an immediate threat to their physical well-being; they may also be concerned about side effects of breast cancer treatments. Indeed, research suggests that symptoms of anxiety and depression are highest at the time of breast cancer diagnosis ( Stafford et al 2013 ). Patients may experience symptoms of shock, disbelief, denial, or despair as they struggle to accept and incorporate the reality of the diagnosis.…”
Section: The Nature Of Psychological Adjustment In Breast Cancer Survmentioning
confidence: 99%
“…Despite the non-pathological nuances of distress, however, a review of the use of the term reveals a considerable overlap with disorder-related concepts of anxiety and depression (Boyes et al, 2013;Carlson et al, 2013;Hegel et al, 2006;Stafford et al, 2013), implying a potential viability of distress being viewed also as a pathological occurrence. Considering this overlap and the large proportion of the patients who are reported to suffer from mental morbidity (Helgeson et al, 2004) distinguishing nonpathological distress responses from potential disorder holds a significant weight further emphasized by its bearing on efficient allocation of available healthcare resources (Narrow et al, 2009).…”
Section: Introductionmentioning
confidence: 95%